2022
DOI: 10.3389/fimmu.2022.814031
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evidence of Variation in Exposure and Immune Response to Bacillus anthracis in Herbivores of Kruger and Etosha National Parks

Abstract: Exposure and immunity to generalist pathogens differ among host species and vary across spatial scales. Anthrax, caused by a multi-host bacterial pathogen, Bacillus anthracis, is enzootic in Kruger National Park (KNP), South Africa and Etosha National Park (ENP), Namibia. These parks share many of the same potential host species, yet the main anthrax host in one (greater kudu (Tragelaphus strepsiceros) in KNP and plains zebra (Equus quagga) in ENP) is only a minor host in the other. We investigated species and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…This study was conducted in central ENP and northern KNP (Figure 2), where the highest incidence of anthrax mortalities is detected within the two parks (Ebedes, 1976; Ochai et al, 2022; Steenkamp et al, 2018). ENP and KNP are located at similar latitudinal ranges and have many species in common.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted in central ENP and northern KNP (Figure 2), where the highest incidence of anthrax mortalities is detected within the two parks (Ebedes, 1976; Ochai et al, 2022; Steenkamp et al, 2018). ENP and KNP are located at similar latitudinal ranges and have many species in common.…”
Section: Methodsmentioning
confidence: 99%
“…There have been reports of a close relationship of pathogenic and non-pathogenic Bacillus spp. resulting in serological cross-reactivity (Marston et al, 2016, Zimmermann et al, 2017) which was also reported in the anthrax endemic region in northern Kruger National Park (KNP) (Steenkamp et al, 2018, Ochai et al, 2022). Anti-PA and LT-neutralising antibodies were also detected at higher rates than expected in animals from a low-incidence area of KNP (southern region) (Ochai et al, 2022).…”
Section: Introductionmentioning
confidence: 79%
“…The KNP (19,485 km 2 ; Figure 1) is situated in the northeastern part of South Africa, bordering Mozambique and Zimbabwe. The northern half of KNP (Figure 1) is considered the anthrax endemic region, where most of the anthrax mortalities have been reported (Ochai et al, 2022, Vos, 1990); this region is classified as semi-arid and is highly wooded with some grassland savannah (Huntley, 1982). KNP has variable elevations, with Pafuri (found in the northernmost part of KNP; 22.4206° S, 31.2296° E) having lower elevation floodplains and mountains towards the northwestern part of the park.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations